Effluent particle removal by microirrigation system filters - Puig-Bargués, J.; Arbat, G.; Barragán, J.; Ramírez de Cartagena, F. (Spanish Journal of Agricultural Research, 2005)
The aim of this work was to determine whether the filters used in microirrigation systems can remove potentially emitter-clogging particles. The particle size and volume distributions of different effluents and their filtrates were established, and the efficiency of the removal of these particles and total suspended solids by screen, disc and sand filters determined. In most of the effluents and filtrates, the number of particles with a diameter > 20 micro m was minimal. By analysing the particle volume distribution it was found that particles larger than the disc and screen filter pores appeared in the filtrates. However, the sand filter was able to retain particles larger than the pore size. The filtration efficiency depended more on the type of effluent than on the filter. It was also found that the particle size distribution followed a potential law. Analysis of the beta exponents showed that the filters did not significantly modify the particle size distribution of the effluents.